Maqashid Analysis of the Phenomenon of Sufi Dance Practices as an Effort to Build Holistic Health on Practitioner in Kartasura - Siti Fathonah; Ernawati Ernawati; Syamsul Bakri (SHAHIH: Journal of Islamicate Multidisciplinary, 2025)
This study aims to describe and analyze the construction of holistic health in Sufi dance, which is considered a human effort to preserve the soul. Holistic health, in anthropology, is a social phenomenon associated with the terminology of illness. Anthropology observes various practices related to how society responds to illness and how to overcome it. Sufi dance is known as a model of healing modified from human-produced art. This study used in-depth interviews and observation as data collection techniques. Through a symbolic analysis typical of anthropology, it was concluded that Sufi dance can function as therapy to build holistic health. There is a close connection between medicine, magic, and religion. Sufi dance is believed to have a health-promoting effect on the performers when they are in a trance state. The Sufi healing process occurs through the stages of bidayah (initiative), namely takhalli, tahalli, and tajalli. In Islamic culture, Sufi dance practices are part of human efforts to implement the maqasid sharia through self-care, which they carry out in Sufi dance practices as Sufi healing. These practices resulted from cultural developments that did not originate from the framework of modern medicine but rather from the framework of classical medicine in the past.